2010
DOI: 10.1021/jf903141s
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose and Raffinose Family Oligosaccharides (RFOs) in Soybean Seeds As Influenced by Genotype and Growing Location

Abstract: Sucrose content in soybean seeds is desired to be high because as a sweetness-imparting component, it helps in wider acceptance of soy-derived food products. Conversely, galactosyl derivatives of sucrose, that is, raffinose and stachyose, which are flatulence-inducing components, need to be in low concentration in soybean seeds not only for augmenting utilization of the crop in food uses but also for delivering soy meal with improved metabolizable energy for monogastric animals. In the present study, analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(121 citation statements)
references
References 14 publications
25
96
0
Order By: Relevance
“…In our experiment, WLM contained comparatively high levels of RSO (8.26 ± 0.14 g/100 g). High amounts of RSOs were also found in SBM, but these levels were lower than those in lupin, which corroborates the findings of other authors (Kumar et al 2010;Svejstil et al 2015). According to Zdunczyk et al (2014), the inclusion of blue lupin seeds (20%) to a layer diet can increase the RSO content (from 0.77 to 2.08% DM).…”
Section: Discussionsupporting
confidence: 89%
“…In our experiment, WLM contained comparatively high levels of RSO (8.26 ± 0.14 g/100 g). High amounts of RSOs were also found in SBM, but these levels were lower than those in lupin, which corroborates the findings of other authors (Kumar et al 2010;Svejstil et al 2015). According to Zdunczyk et al (2014), the inclusion of blue lupin seeds (20%) to a layer diet can increase the RSO content (from 0.77 to 2.08% DM).…”
Section: Discussionsupporting
confidence: 89%
“…The specific availability of raffinose in mucosal secretions has not been determined. Raffinose and stachyose are common galactooligosaccharides, found in large amounts in plants and plant products used as staple human foods, such as beans and soy (11,26). They are not fermented by our bodies but are thought to be substrates for the intestinal microflora (50).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, KarrLilienthal et al (2004) reported that pigs fed diets containing SBM from India had lower CP digestibility. It has been reported that different growing conditions and the use of various soybean genotypes in different regions can affect nutrient composition, including contents of oligosaccharides, protease inhibitors and fiber (Kumar et al, 2010;Baker and Stein, 2009). As a result, nutrient digestibility in different batches of SBM fed to pigs may differ (Karr-Lilienthal et al, 2005).…”
Section: Nutrient Digestibilitymentioning
confidence: 99%